Flexibility in Javanese Folk Performing Arts: Adaptation, Creation, and Innovation - Kiswanto, Kiswanto; Paimin, Paimin; Prihatin, Wahyu (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2026)
This study aims to uncover and explain the concept and model of flexibility as a mechanism for the sustainability of folk performing arts amidst conditions of social and cultural change. The study was conducted using an ethnographic approach, based on participatory and collaborative activities within the Turonggo Seto Boyolali group, and supported by data collection techniques including observation, interviews, documentation, and literature review. The results of this study indicate that flexibility is a principle and approach applied through the process of adaptation, creation, and innovation. This process is carried out to preserve and develop traditional performing arts, ensuring they continue to exist and evolve amid changes in their social and cultural context. Adaptation, creation, and innovation in the form and variety of artistic presentations are carried out by considering several aspects, namely the development of aesthetic needs (tastes) of performing artists, audience segmentation (social and market), the needs or requirements of the performance organization, and the spatial and temporal context of the performance organization. The process occurs through the practice of diversification and differentiation of artworks, followed by developments in almost every type of artwork. The results of this process make the TSB group more flexible in determining and selecting the types of artworks to be offered and presented for performance. In general, folk performing arts performances are divided into Full Performance Formats and Limited Performance Formats.